From Biomass-Derived p-Hydroxycinnamic Acids to Novel Sustainable and Non-Toxic Phenolics-Based UV-Filters: A Multidisciplinary Journey - Rioux, Benjamin; Combes, Jeanne; Woolley, Jack M.; Rodrigues, Natércia d. N.; Mention, Matthieu M.; Stavros, Vasilios G.; Allais, Florent (Frontiers in Chemistry, 2022)
Although organic UV filters are extensively used in cosmetics to protect consumers from the deleterious effects of solar UV radiation-exposure, they suffer from some major drawbacks such as their fossil origin and their toxicity to both humans and the environment. Thus, finding sustainable and non-toxic UV filters is becoming a topic of great interest for the cosmetic industry. A few years ago, sinapoyl malate was shown to be a powerful naturally occurring UV filter. Building on these findings, we decided to design and optimize an entire value chain that goes from biomass to innovative biobased and non-toxic lignin-derived UV filters. This multidisciplinary approach relies on: (1) the production of phenolic synthons using either metabolite extraction from biomass or their bioproduction through synthetic biology/fermentation/in stream product recovery; (2) their functionalization using green chemistry to access sinapoyl malate and analogues; (3) the study of their UV-filtering activity, their photostability, their biological properties; and (4) their photodynamics. This mini-review aims at demonstrating that combining biotechnology, green chemistry, downstream process and photochemistry is a powerful approach to transform biomass and, in particular lignins, into high value-added innovative UV filters.